Tuberkulosis di Indonesia: Apakah Status Sosial-Ekonomi dan Faktor Lingkungan Penting? - Kusumaningrum, Amalia; Wulandari, Grace; Kautsar, Achmad (UI Scholars Hub, 2023)
This study aims to find the social-economic status and environmental factors for tuberculosis in Indonesia by using Indonesia Family Life Survey (IFLS) data in 2014. First, this study analyzes individual characteristics with regression logistic method. Second, this study estimating social-economic status by entering a correction from the first stage. Meanwhile at the third stage, adding factors home environmental conditions and entering a correction from the previous stage. This study find that household income is the affecting factors, especially for households with incomes of less than IDR 600.000. In additions, level education especially high school and college also has a significant effect on tuberculosis. Meanwhile, the environmental factors did not have a significant effect on tuberculosis.